Komunitas dan Unit Kegiatan Mahasiswa Dalam Proses Mencapai Prestasi Non Akademik - Bambang Sugito; Jajuk Dwi Sasanadjati; Arif Hidajad; Budi Dharmawan Putra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article discusses the results of research including organizational capabilities in achieving professionalism related to activities that manage the organization to channeling student abilities that support lectures. The department's efforts in providing a forum for various organizations formed by students are able to make a positive contribution to students, departments, faculties and universities. Because based on the organization of activities formed in two categories, namely student activity units and student activity communities, they are able to provide positive results to the agencies that oversee these activities. The process of organizational achievement has not been distinguished between activity units and activity communities so that there are many process constraints faced by activity organizations. There is an increase in organizational management related to the priority scale in the results achieved. If it is able to reach the national or international level, the organization must be under the auspices of the university. If the organization is not able to compete at the national or international level, it will be lowered under the auspices of the Faculty. This will make it easier to manage the resources that are achieved. The process of achieving maximum competition has not been in accordance with the appreciation of the organization because it collided with an adequate allocation of funds. Students have to struggle starting from energy, mind and even having to spend money to cover the various deficiencies that are made in the process.